Biological Resistance of Jabon Wood Against Subterranean and Drywood Termites after Combined Impregnation and Compression Treatment - Jamaludin Malik (Wood Research Journal, 2022)
This study investigated Jabon wood [Anthochepalus cadamba (Roxb) Miq) impregnated with natural phenolic resin from Merbau extractives (ME) and subjected to hot compression treatments. The resistance of this wood to subterranean termites (Coptotermes curvignathus Holmgren) and drywood termites (Cryptotermes cynocephalus Light) was tested. The types of pre-treatments utilized were impregnation, repeated-impregnation, hot compression, and a combined treatment of impregnation and hot compression. The impregnation pre-treatment used crude ME and selected polymerized ME (PME22 and PME33). The resistance evaluation was based on the weight loss of the samples according to the Indonesian standard of SNI 7207 (2014). Untreated samples of jabon were classified as grade V (susceptible) against subterranean termites and grade IV (non-resistant) against drywood termites. Impregnation using only ME improved the resistance of Jabon wood against subterranean termite from grade V to grade IV. Against drywood termites, it changed from class IV to III and II. The resistance class of III against subterranean termites resulted from the treatments of various schedules of polymerized ME. Thus, the extractives contributed greatly to the protection of a less durable wood species against termite attack. Merbau extractives also distinctly improved the resistance of jabon wood from grade IV (non-resistant) to grade II (resistant).